Memória e identidade em O feminino e o sagrado, de Julia Kristeva e Catherine Clément - Tatiana Paula Leal Bernardes (2021)
This study aims to work on the relationships between women and the sacred presented in Catherine Clément’s and Júlia Kriteva’s book The feminine and the Sacred. The book in question consists of the correspondence between the authors, which took place from November 1996 to October 1997. In the correspondence, the authors discuss the feminine position in relation to sacred environments and analyze how these positions interfere in the relationship of women with the divine and in women’s social position. In this dissertation, in addition to discussing these issues, we will also analyze the use of letters as a vehicle for these questions made by the authors and the memory used in epistolary writing. Another important point for this discussion is the fact that the relationship between women and deities can, in some cases, go beyond the religion, something that is also extremely relevant for the proposed discussion. Therefore, the concept of hierogamy will also be worked on. The entire analysis presented here is part of a long bibliographic search, based on texts by researchers who were also interested in epistolography, memory, female social position and human relations with deities.